Ensuring Food Security and Human Security: An Assessment of the Security Challenges in India - Nagendra Nath Gogoi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The poor and the vulnerable people in developing countries like India are the ones which are seriously affected by limited or even no access to food. This situation demands for a revision of the concept of food security in recent times. Though India’s economic growth has been remarkable in last few years except current situation, the country is still struggling with extreme hunger and poverty. Around 14.8 percent of the population In India is undernourished, as per the FAO estimates in the ’State of Food Security and Nutrition in the World, 2018’ report. It is therefore essential to investigate the status of food security in India from the perspective of human security. This paper is an attempt to assess the Security Challenges and policies for ensuring food security in India.